COMPARISON OF LEARNING OUTCOMES USING PROJECT-BASED LEARNING MODEL VERSUS CONVENTIONAL LEARNING IN ELEMENTARY SCHOOL - Agus Hidayat; Darmawanta Sembiring; Hudson Sidabutar (Indonesian Journal of Education (INJOE), 2024)
This observation aims to compare learning outcomes among students who apply the Project-Based Learning (PJBL) Model with those who learn through conventional means in elementary schools. The research method utilized the literature study method. The findings indicated that students who learned through the PjBL model generally achieved better learning outcomes in terms of critical thinking, creativity and problem-solving skills. The PjBL model also appeared to increase students' motivation and enthusiasm for learning as they were more engaged in relevant and interesting projects. In addition, PjBL facilitates the development of better social skills and teamwork through collaboration and interaction among students in project groups. Nevertheless, this study also found some challenges in implementing PjBL in primary schools, such as the need for more thorough preparation, longer implementation duration, and the need for special training for teachers. Therefore, in order to maximize learning outcomes, it is suggested that a wise mix of PjBL and conventional learning models is needed in accordance with educational objectives and students' needs.